PENGELOLAAN KEUANGAN DAERAH TERHADAP PERTUMBUHAN EKONOMI KABUPATEN/KOTA DI SUMATERA BARAT PADA ERA DESENTRALISASI FISKAL - Rahmat; Yollit Permata Sari (Universitas Negeri Padang, 2025)
Economic growth is one of the indicators used to measure a country's success. The government plays an important role in accelerating economic growth. The government implements various policies to increase economic growth. One part of fiscal policy is government spending, which the government uses to regulate the economy by determining its revenue and expenditure each year.The purpose of this study is to determine the quality of regional financial independence, the quality of regional financial effectiveness, the quality of regional financial efficiency on the economic growth of West Sumatra Province in the era of fiscal decentralization. The method in this study uses a quantitative method, using time series data, This study focuses on districts/cities in West Sumatra Province. The results of this study are that the level of effectiveness has a negative and insignificant effect on economic growth. The level of efficiency has a positive and significant effect on economic growth. The level of independence has a negative and significant effect on economic growth in West Sumatra Province and vice versa. The variables of effectiveness ratio, efficiency ratio, independence ratio of regional financial management, revenue growth acceleration ratio and simultaneously have a significant influence with a positive direction on economic growth in West Sumatra Province. The conclusion of this study means that the three independent variables together are able to increase economic growth in West Sumatra Province. A statistical model explains 47% of the dependent variable, namely economic growth, through independent variables. The independent variables are effectiveness, efficiency, and independence. The remaining 53% is explained by factors outside the model.